(untitled) (Pedagogical Horizons, 2021)
If learners experience pressure at school, the reduced autonomy-support has a detrimental effect on students’ learning motivation, school performance, and well-being (Ryan & Deci, 2017). In this study, we examine whether the motivational experiences varied between the samples before and during the Corona pandemic (the later focusing on the early fall 2020). Based on two surveys (n1 = 302; n2 = 304) with students aged 13 and 19 years, a quantitative analysis measured the difference for the scales of perceived autonomy, school-related pressure and subjective vitality. In addition, a qualitative analysis on the open-end question regarding school pressure was conducted in order to identify factors that put students under pressure and to determine, whether these have been reinforced or shifted by the Corona pandemic. Except for an increase for the factor “fears about the future”, no significant changes were observed. The high and constant impact of the factors "achievement" and "fear of failure" are discussed providing didactic considerations for teachers to create more favorable motivational settings for learners.